2023
DOI: 10.1099/ijsem.0.005672
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of the genus Alcanivorax: proposal for division of this genus into the emended genus Alcanivorax and two novel genera Alloalcanivorax gen. nov. and Isoalcanivorax gen. nov.

Abstract: The members of the genus Alcanivorax are key players in the removal of petroleum hydrocarbons from polluted marine environments. More than half of the species were described in the last decade using 16S rRNA gene phylogeny and genomic-based metrics. However, the 16S rRNA gene identity (<94 %) between some members of the genus Alcanivorax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Furthermore, strains SYSU D00823 T , SYSU D00873 T and P. xinjiangensis CCTCC AB 208092 T showed 56.7-57.3 % POCP values with P. mongoliensis KCTC 52859 T . Although a 50 % POCP cut-off value was proposed for defining bacterial genera [23], it has been shown that this universal cut-off is too conservative to be appropriate for circumscribing many bacterial genera [31][32][33]. The detailed paired overall genome relatedness indices (OGRIs) are shown in Table 2.…”
Section: Genome Featuresmentioning
confidence: 99%
“…Furthermore, strains SYSU D00823 T , SYSU D00873 T and P. xinjiangensis CCTCC AB 208092 T showed 56.7-57.3 % POCP values with P. mongoliensis KCTC 52859 T . Although a 50 % POCP cut-off value was proposed for defining bacterial genera [23], it has been shown that this universal cut-off is too conservative to be appropriate for circumscribing many bacterial genera [31][32][33]. The detailed paired overall genome relatedness indices (OGRIs) are shown in Table 2.…”
Section: Genome Featuresmentioning
confidence: 99%
“…A. borkumensis [27] is classified within the order Oceanospirillales of the class of the Gammaproteobacteria. Recent phylotaxogenomic analysis [16S rDNA sequencing, DNA-DNA Hybridization (dDDH), Average Nucleotide Identity (ANI), Average Amino Acid Identity (AAI), Percentage of Conserved Proteins (POCP) and comparative genomic studies [20,28] showed that Alcanivorax species formed three clades named Isoalcanivorax gen. nov. and Alloalcanivorax gen. nov., respectively, along with the emended description of the genus Alcanivorax sensu stricto (Table 1).…”
mentioning
confidence: 99%